Pathologic up-regulation of TNFSF15–TNFRSF25 axis sustains endothelial dysfunction in unprovoked venous thromboembolism. Issue 3 (28th May 2019) - Della Bella, Silvia; Calcaterra, Francesca; Bacci, Monica; Carenza, Claudia; Pandolfo, Chiara; Ferrazzi, Paola; Uva, Paolo; Pagani, Massimiliano; Lodigiani, Corrado; Mavilio, Domenico
Abstract: Aims: The pathogenetic mechanisms underlying unprovoked venous thromboembolism (uVTE) are largely unknown. In this study, we investigated the molecular mechanisms involved in uVTE pathogenesis by using ex vivo expanded endothelial colony-forming cells (ECFCs), which represent a valuable non-invasive tool for the assessment of endothelial function. Methods and results: We isolated and expanded ECFCs from the peripheral blood of uVTE patients and observed that these cells underwent earlier senescence and showed lower growth rate compared with ECFCs obtained from healthy donors. Through microarray expression profiling, we demonstrated that 2905 genes were differentially expressed between patients and controls. Among them, the anti-angiogenic cytokine TNF superfamily member 15 (TNFSF15) and its death-receptor TNFRSF25 were up-regulated in uVTE ECFCs, and this finding was validated by RT-qPCR. TNFSF15 up-regulation was confirmed at the protein level in ECFC supernatants, and the in vivo relevance of these findings was further corroborated by demonstrating that also the plasmatic levels of TNFSF15 are increased in uVTE patients. After proving that exogenous TNFSF15 exerts pro-apoptotic and anti-proliferative activity on control ECFCs, we demonstrated through blocking experiments that TNFSF15 up-regulation contributes to impaired survival and proliferation of uVTE ECFCs. Conclusion: By providing evidence that TNFSF15 impairs ECFC functions crucial to endothelial repair, and that uVTE patients have increased TNFSF15 levels both ex vivo and in vivo, the results of this study suggest that pathologic up-regulation of TNFSF15–TNFRSF25 axis may contribute to uVTE pathogenesis, and may represent the target for novel therapeutic strategies aimed at preventing recurrences in uVTE patients.